Slawter - Shan, Darren (New York : Little, Brown and Company, 2006)
While on a horror movie set with his Uncle Dervish, Grubbs Grady realizes that his battle with the evil demon master Lord Loss may be about to resume
Keywords: Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Motion pictures -- Juvenile fiction; Horror stories